Multiculturalismo y comunicación: disertaciones teóricas y propuestas - Martínez Lozano, Consuelo Patricia; Dominguez, Daniel Solís (Revista Extraprensa, 2013)
The objective of this text is to reflect on the links between the communication environment and the multicultural contexts. These relations represent an analysis field that must be approached, because somehow, in those interconnections excellent forms of socialization are defined, like the building of the individual identity as much as collective. The links, between the multiculturalism and the communication, imply processes where power is a transverse axis and is a part of the structure of such relation. The tex is a proposal for a research agenda about the communication analyses with a multicultural perspective. Among the various manifestations of multiculturalism, four aspects were developed: gender, religion, generational differences and ethnicity. In the text there is a theoretical position in regard to the multiculturalism, this is understood from a critical and reflexive perspective, oriented towards actions that allow to make changes in the domination/subvordination relations according to situations, agents, relationships and specific context, built historically.